The minimum water consumption of ethanol production via biomass fermentation - Pfromm, Peter H. (My University, 2008)
The water consumption of fermentation-based bio-ethanol production has recently begun to attract public attention. We calculate a minimum consumption of 2.85 gal water/gal of ethanol produced assuming zero liquid discharge and otherwise current industrial practice data. Including cooling tower blowdown and drift this value may increase to on the order of 4 gal water/gal of ethanol produced. Reduction of the thermal energy input to the process is vital to reduce this irretrievable water consumption.
Keywords: Ethanol; Water demand; Bio-ethanol; Cooling water; Minimum water demand